Histopathological features of equine superficial, nonhealing, corneal ulcers. (31st October 2013) - Hempstead, Julie E.; Clode, Alison B.; Borst, Luke B.; Gilger, Brian C.
Abstract: Objective: To evaluate corneal changes associated with chronic, nonhealing, superficial, corneal ulcers in horses via common histopathological stains. Design: Retrospective study. Animals: Twenty‐four horses diagnosed with chronic, nonhealing, superficial, corneal ulceration. Methods: The medical records of horses evaluated at North Carolina State University's Veterinary Teaching Hospital (NCSU‐VTH) from 2005 to 2011, diagnosed with a chronic, nonhealing, superficial, corneal ulcer and treated with superficial keratectomy (SK) were reviewed. Inclusion criteria were superficial corneal ulceration, no cellular infiltration via slit‐lamp biomicroscopy, no microorganisms evident on corneal cytology, and acquisition of samples for aerobic bacterial and common fungal cultures. Corneal tissue samples were evaluated histopathologically for the presence or absence of a nonadherent epithelial 'lip', epithelial dysmaturity, intraepithelial inflammatory cells, an acellular hyaline zone in the anterior stroma, and stromal inflammatory cells, fibrosis and vascularization. Results: In the majority of analyzed samples, epithelial cells adjacent to the ulcerated site showed nonadherence to the basement membrane and dysmaturity. Intraepithelial inflammatory cell infiltration was uncommon. Histopathological features of an anterior stromal hyaline zone, intrastromal inflammation, fibrosis and vascularization were variably present. Conclusions: The most consistent histopathological characteristics of equine chronic, nonhealing, superficial, corneal ulcers include epithelial nonadherence, epithelial dysmaturity and mild to moderate stromal inflammation; however, one set of histopathological characteristics does not definitively define this syndrome in horses. Additionally, the anterior stromal acellular hyaline zone commonly cited in canine spontaneous chronic corneal epithelial defects (SCCED) is not a consistent finding in equine corneas.